2014
DOI: 10.1093/jnci/dju090
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells Loaded With Multimechanistic Oncolytic Herpes Simplex Virus Variants for Brain Tumor Therapy

Abstract: Human MSC loaded with different oHSV variants provide a platform to translate oncolytic virus therapies to clinics in a broad spectrum of GBMs after resection and could also have direct implications in different cancer types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 37 publications
1
81
0
Order By: Relevance
“…Our results indicate that human MSCs loaded with different oHSV variants provide a platform to translate OV therapies to clinics in a broad spectrum of GBMs after resection and could also have direct implications in different cancer types (Duebgen et al, 2014). These studies confirm the feasibility of using MSCs as carriers for OV therapy.…”
Section: Stem Cell -Oncolytic Virus Therapysupporting
confidence: 73%
“…Our results indicate that human MSCs loaded with different oHSV variants provide a platform to translate OV therapies to clinics in a broad spectrum of GBMs after resection and could also have direct implications in different cancer types (Duebgen et al, 2014). These studies confirm the feasibility of using MSCs as carriers for OV therapy.…”
Section: Stem Cell -Oncolytic Virus Therapysupporting
confidence: 73%
“…Given that delivery of therapeutic agents to the tumors in the brain is a major challenge, significant efforts have been made to develop efficient delivery routes to brain tumors, which include both invasive and noninvasive administration strategies (42). In a previous study, we showed that local implantation of encapsulated MSCs loaded with oHSV have therapeutic efficacy in mouse models of resected brain tumors (21). Recent studies have shown that i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory demonstrated that therapeutic human and mouse stem cells home extensively to multiple tumor deposits in the brain (20) and act as cell carriers for onsite delivery of tumor-specific agents or OV (21) in mouse models of different brain tumor types (22). In the present study, we tested the therapeutic efficacy of MSC-loaded oHSV (MSCoHSV) in both BRAF mutant and WT in vivo imageable mouse models of melanoma brain metastasis, and explored the combined therapeutic efficacy of PD-L1 blockade and MSC-oHSV in a syngeneic mouse model of melanoma brain metastasis.…”
Section: Significancementioning
confidence: 99%
“…Mesenchymal Stem Cells (MSCs) loaded with oncolytic herpes simplex virus (oHSV) have recently been shown to be effective and provide a significantly higher benefit in glioma-bearing mice compared to pure oHSV [102]. Despite good preclinical results, the clinical application of stem cells as carriers of brain-targeted therapy is still controversial.…”
Section: Accepted Manuscriptmentioning
confidence: 99%